Simulation of a natural gas TEG dehydration plant - Carollo, Cristina (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ). Εργαστήριο Θερμοδυναμικής και Φαινομένων Μεταφοράς, 2018)
Natural gas is saturated with water at reservoir conditions. For this reason it is necessary to remove it to avoid operational problems, such as corrosion, hydrate formation or slug flow, during the transportation or processing of natural gas. This is usually obtained by dehydration, which is a process thanks to which water is removed from the gas to prevent its condensation under high pressure or low temperature conditions. Typically, in offshore units, dehydration by some glycol desiccant, usually triethylene glycol (TEG), occurs. Although it is a generally used procedure in industrial practice, several parameters affect its efficiency, such as the glycol circulation rate, the operating conditions of the columns, the way by which the purity of the glycol is enhanced during regeneration etc. In particular, since it is not possible to work close to TEG boiling point, the lean TEG purity required by the absorption process is obtained in the regeneration section with enhanced methods, as the addition of stripping gas or setting vacuum conditions in the distillation column. For this reason, in this work, a sensitivity analysis of several operating variables of the process has been conducted. Namely, the effect of the temperature and pressure of the glycol contactor and regenerator, the temperature obtained after the heat exchangers and the stripping gas rate. This has been achieved by simulating a typical dehydration unit, based on conditions taken from the literature, in the Aspen HYSYS vs 8.8. environment. For the simulation two different thermodynamic models have been considered. That is the proposed by HYSYS for the use in dehydration TST-NRTL model and the UMR-PRU model which has been developed in the thermodynamics and transport phenomena laboratory and is known to yield satisfactory results for natural gas mixtures and it is implemented into HYSYS through the CAPE-OPEN 1.1 protocol. From the sensitivity analysis, it has been established that an increase of the flash drum temperature and of the temperature of the stream which enters at the regenerator leads to a lower water content, with decrease of the required duties at the same time. For that reason, an optimization of the process in terms of required duties has been conducted. The optimization occurred on the basis of a 30 ppm water content in the dry gas, as the required specification, which occurred using the stripping gas rate as independent variable. It is resulted that by increasing the temperature of the stream entering the regenerator to 137oC and the flash drum temperature to 100oC for the TST-NRTL or 90oC for the UMR-PRU, there is an 9% decrease to the required reboiler duty for the first and a 8.2% decrease for the latter. This is also reflected to a 21% decrease in the stripping gas rate for the first and a 26% for the second. The cooler duty decreases as well at the optimized conditions, with a difference of 17% for TST-NRTL model and 14% with UMR-PRU. Instead, the duties of the two pumps are almost the same for both operating conditions. Following the results of the sensitivity analysis, a preliminary economic evaluation of the unit is conducted in terms of installed and operating cost. The economic evaluation occurs for both the initial considered case and the optimized one, for each of the examined thermodynamic models. It is concluded that there is an about 5% difference between the obtained by HYSYS capital cost and the cost calculated through generalized correlations for each part of the equipment, while no significant difference is observed between base and optimized conditions. All obtained values are considered inside the uncertainty of the calculations and in good accordance with the available literature data, since the deviation in the case of the optimized simulation with UMR-PRU model is about 15 %, from the latter. Considering the operational costs, instead, a 8% decrease is obtained for the optimized conditions for the TST-NRTL model and 7% for the UMR-PRU, which corresponds to a saving of about 15700$/year. Finally, the simulation of the dehydration of a real gas mixture occurred. It is concluded that both models are able to meet the required specification of 30 ppm of water content in the dry gas, yielding similar results with those observed in the synthetic gas case. The models differ in the calculated stripping gas rate. Actually, TST-NRTL results in higher stripping gas rate compared to UMR-PRU. The models differ, also, in the heavier components distribution in the glycol-rich streams, with UMR-PRU to result generally in higher hydrocarbon loss. The same is valid for the calculated TEG loss. From all the examined cases, it has been shown that the difference between the models is more profound in the calculated duties, where UMR-PRU systematically yields lower duty compared to TST-NRTL. Due to the better prediction of the aqueous TEG mixture heat capacity with the UMR-PRU model, its predictions in terms of duties are expected to be closer to the actual process data. Furthermore, UMR-PRU results in higher hydrocarbon loss in glycol-rich streams and higher TEG loss in the vapor stream which are closer to the corresponding phase equilibrium data. Overall, it is concluded that the UMR-PRU model yields better results than the proposed by HYSYS TST-NRTL model in the simulation of a TEG dehydration unit.